The solution to given equation 2x + 10 -6 = 2 is x = -1
Solution:
Given that the equation is:
2x + 10 -6 = 2
We have to find solution to the equation. Which means we have to solve and find value of "x"
Let us first simplify the given equation
2x + 10 - 6 = 2
Let us use BODMAS rule to perform sequence of arithmetic operations
According to BODMAS rule, if an expression contains brackets ((), {}, []) we have to first solve or simplify the bracket followed by of (powers and roots etc.), then division, multiplication, addition and subtraction from left to right
So first perform subtracting 6 from 10
2x + 4 = 2
Let us move the term "4" from L.H.S to R.H.S
2x = 2 - 4
Now perform addition of 2 and -4
2x = -2
![x = (-2)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9m9pbf5btvx4no8ou3xvwbu3ooso3ztrrd.png)
Now perform division operation
x = -1
Thus the solution to given equation is x = -1